Stroke Severity Scale to Palliative Screening, Activity Daily Living (ADL) Impairment, and Quality of Life - Arlies Zenitha Victoria; Sri Puguh Kristiyawati; Anna Jumatul Lely (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Palliative care is needed for various diseases; stroke is one of the neurological diseases that requires palliative care. Stroke is one of the leading causes of disability and decreased quality of life due to neurological deficits. The National Institute of Health Stroke Scale (NIHSS) assesses stroke severity. Stroke can also cause paralysis, resulting in decreased independence in self-care; patients will experience difficulty carrying out daily activities or activities of daily living (ADL) such as walking, dressing, eating, or controlling defecation or urination. Disability due to stroke can affect the patient's quality of life. Objectives: This study aimed to analyze the relationship between stroke severity scale with palliative screening, activities of daily living impairment (ADL), and quality of life. Methods: This cross-sectional study involved sixty stroke patients selected by accidental sampling. The data were analyzed using Pearson Product Moment and Spearman Rank Test. Results: This study resulted in 53,3% of respondents suffering from a moderate stroke, 90,0% needing palliative intervention, 56,7% total dependency, and 66,7% can not assess quality of life. Significance level between stroke severity scale with palliative screening ware (p=0,000), ADL impairment (p=0,008), and quality of life (p=0,000). Conclusions: There was a relationship between the stroke severity scale and palliative screening, activities of daily living (ADL) impairment, and quality of life. Further research should simultaneously analyze the risk factors for stroke, the stroke severity scale, and things that are influenced by the severity of the stroke so that it can be seen which variable is more dominant.